Causes of blindness in people aged 50 years and over: community-based versus hospital-based study - Al-Akily, Saleh A.; Bamashmus, Mahfouth A.; Al-Mohammadi, Khaled A. (World Health Organization, Regional Office for the Eastern Mediterranean, 2010)
The causes of blindness in Yemen were determined in people aged 50+ years in both a communityand hospital-based study and documented using WHO/PBL criteria. In the community sample of 707 individuals in a rural area of Taiz governorate the prevalence of bilateral blindness was 7.9% and the main causes were cataract [71.4%] and age-related macular degeneration [ARMD] [14.3%]. Corneal opacities and uncorrected aphakia were rare [1 case each] and there were no cases of diabetic retinopathy. Unilateral blindness was found in 8.6% of the community sample. In a case-notes review of 1320 new patients attending an eye clinic in Sana'a, bilateral blindness was documented in 26.5% and unilateral blindness in 9.0% [main causes: cataract, glaucoma, ARMD, diabetic retinopathy, corneal opacities and trauma